Correspondence Between Resting-State and Episodic Memory-Task Related Networks in Elderly Subjects - Simon-Vermot, Lee; Taylor, Alexander N. W.; Araque Caballero, Miguel À.; Franzmeier, Nicolai; Buerger, Katharina; Catak, Cihan; Janowitz, Daniel; Kambeitz-Ilankovic, Lana M.; Ertl-Wagner, Birgit; Duering, Marco; Ewers, Michael (Frontiers in Aging Neuroscience, 2018)
Resting state fMRI studies demonstrated temporally synchronous fluctuations in brain activity among ensembles of brain regions, suggesting the existence of intrinsic functional networks. A spatial match between some of the resting-state networks and regional brain activation during cognitive tasks has been noted, suggesting that resting-state networks support particular cognitive abilities. However, the spatial match and predictive value of any resting-state network and regional brain activation during episodic memory is only poorly understood. In order to address this research gap, we obtained fMRI acquired both during rest and a face-name association task in 38 healthy elderly subjects. In separate independent component analyses, networks of correlated brain activity during rest or the episodic memory task were identified. For the independent components identified for task-based fMRI, the design matrix of successful encoding or retrieval trials was regressed against the time course of each of the component to identify significantly activated networks. Spatial regression was used to assess the match resting-state networks against those related to successful memory encoding or retrieval. We found that resting-state networks covering the medial temporal, middle temporal and frontal areas showed increased activity during successful encoding and networks situated in posterior brain regions were related to successful recognition. However, the level of resting state network connectivity was not predictive of the task-related activity in these networks. These results suggest that particular intrinsic networks become engaged successful episodic memory, but higher intrinsic connectivity at rest may not translate into higher network expression during episodic memory.